Cyber-Theology of The Polis: Renegotiating The Ethics of Participation In The Age of AI - Rahmadhani, Danu Saifulloh (Journal for the study of religions and ideologies, 2025)
In the digital age, the interplay of technology, theology, and politics presents novel challenges to public morality. Cyber-theology of the Polis offers a normative framework integrating ethics, spirituality, and digital realities. This study addresses the rise of cyberculture by developing cybermorality—an ethical approach to technology use that upholds human dignity. The research employs conceptual analysis to examine and harmonize key concepts in theology, ethics, and digital technology. Digital technology carries an ambivalent impact: while it enhances transparency, it also threatens democratic accountability through algorithms and cyberactivism. Principles of digital justice and agency integrity are emphasized to ensure fair, inclusive, and humane political participation. Furthermore, truth as relationship rejects reducing truth to mere data, stressing the critical importance of trust in the digital sphere. Theology serves as a prophetic voice against algorithmic dominance, providing an ethical-spiritual framework for a just, autonomous, and dignified digital society.